Contribution of oxidative stress to endothelial dysfunction in hypertension - Silva, Bruno R.; Pernomian, Laena; Bendhack, Lusiane M. (Frontiers in Physiology, 2012)
Endothelial dysfunction is the hallmark of hypertension, which is a multifactorial disorder. In the cardiovascular system reactive oxygen species play a pivotal role in controlling the endothelial function and vascular tone. Physiologically, the endothelium-derived relaxing factors (EDRFs) and endothelium-derived contractile factors (EDCFs) that have functions on the vascular smooth muscle cells. The relaxation induced by the EDRFs nitric oxide (NO), prostacyclin, and the endothelium-derived hyperpolarization factor (EDHF) could be impaired in hypertension. The impaired ability of endothelial cells to release NO along with enhanced EDCFs production has been described to contribute to the endothelium dysfunction, which appears to lead to several cardiovascular diseases. The present review discusses the role of oxidative stress, vascular endothelium, and vascular tone control by EDRFs, mainly NO, and EDCFs in different models of experimental hypertension.